Long-term effects of endoscopic papillary large balloon dilation in patients with challenging bile duct calculi: A retrospective observational study. Issue 36 (10th September 2021) - Kamezaki, Hidehiro; Iwanaga, Terunao; Maeda, Takahiro; Senoo, Jun-ichi; Sakamoto, Dai; Yasui, Shin; Sugiyama, Harutoshi; Tsuyuguchi, Toshio; Kato, Naoya
Abstract : Abstract: Endoscopic papillary large balloon dilation (EPLBD) can be used to treat challenging common bile duct stones. No previous studies have reported intractable cases treated either by EPLBD or mechanical lithotripter use. We aimed to evaluate and compare the long-term effects of EPLBD with mechanical lithotripter use. This retrospective cohort study reviewed data from 153 patients admitted to the Eastern Chiba Medical Center from April 2014 to March 2020, presenting with common bile duct calculi that could not be removed using a basket or balloon catheter. Patients were divided into groups depending on whether the treatment was performed using a mechanical lithotripter or EPLBD. The primary outcome was the recurrence rate of common bile duct calculi, and the secondary outcome was the rate of postoperative adverse events. The Wilcoxon test was used to compare the 2 groups. Statistical significance was set at P < .05. The median age of patients included in the lithotripter and EPLBD groups were 73 years and 83 years, respectively ( P = .006), while the sex ratio (male:female) in the groups was 18:13 and 55:67, respectively. The EPLBD group showed a statistically larger median bile duct diameter (13 mm [range: 8–24 mm] vs 11 mm [range: 5–16 mm]; P < .001), larger maximal calculus diameter (median, 13.5 mm [range: 8–25 mm] vs 11 mm [range: 7–16 mm]; P < .001), and shorter median cumulative treatment time after reaching the duodenal papilla (35.5 minutes [range: 10–176 minutes] vs 47 minutes [range: 22–321 minutes]; P = .026) in comparison to the lithotripter group. There was no significant difference in the rate of adverse events between the EPLBD and the mechanical lithotripter groups. The recurrence rate was significantly lower ( P = .014) in the EPLBD group. EPLBD increases therapeutic efficacy and reduces treatment duration for patients in whom calculus removal is difficult, without increasing the frequency of adverse events. No serious adverse events were observed. Additionally, EPLBD appears to reduce the risk of long-term recurrence. Future studies are needed to evaluate long-term outcomes in younger patients.